2004
DOI: 10.1111/j.1365-2141.2004.04957.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of functional plasma haemostasis proteins in long‐term primary cultures of human hepatocytes

Abstract: Summary This study was designed to investigate the ability of long‐term primary cultures of adult human hepatocytes to secrete the main haemostasis proteins. Factors II, V, VII, VIII, PIVKA‐II (protein induced by vitamin K 1 absence or antagonist II), fibrinogen and antithrombin were quantified in culture medium by immunological methods and by measuring the coagulant activity of factors II, V and VII. All the haemostasis protein antigens except the factor VIII antigen (FVIII:Ag) were found in the culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…This cellular model closely mimics the physiological situation. Indeed, we have shown that these cultures retain several liver phenotypic markers including secretion of plasma proteins [31] and blood coagulation factors [30], expression and inducibility of detoxification enzymes [33,34,42,43], expression of C/EBP transcription factors [32], activation of cytokine signal transmission [29,35], and are sensitive to infection by HCV or hepatitis delta virus and permissive to their genome replication [35][36][37]. Intracellular accumulation of replicative and genomic HCV RNA strands, assessed by rTth-RT-PCR and quantitative RT-PCR [35,36,38,39], respectively, were used as experimental end points.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This cellular model closely mimics the physiological situation. Indeed, we have shown that these cultures retain several liver phenotypic markers including secretion of plasma proteins [31] and blood coagulation factors [30], expression and inducibility of detoxification enzymes [33,34,42,43], expression of C/EBP transcription factors [32], activation of cytokine signal transmission [29,35], and are sensitive to infection by HCV or hepatitis delta virus and permissive to their genome replication [35][36][37]. Intracellular accumulation of replicative and genomic HCV RNA strands, assessed by rTth-RT-PCR and quantitative RT-PCR [35,36,38,39], respectively, were used as experimental end points.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, primary cultures of highly differentiated human hepatocytes [29][30][31][32][33][34] are likely to represent the most physiologically relevant model to investigate serum-derived HCV infection. Indeed, previous studies have shown that human hepatocytes are sensitive to infection by HCV or hepatitis delta virus and permissive to their genome replication [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it recently was demonstrated that significant synthesis of the coagulation factor FVIII by hepatocytes in culture only occurs in the presence of vWF derived from ECs. 46 Thus, similar coordinated mechanisms may regulate the production of stimulatory cytokines and growth factors in our coculture system.…”
Section: Discussionmentioning
confidence: 99%
“…Liver regeneration appears to adversely affect the production of other liver-specific proteins not directly involved in the regenerative process, including albumin and ornithine transcarbamylase. In terms of hemostasis, the production and secretion of the coagulation factors, anti-coagulant factors, and fibrinolytic factors are highly dependent on the hepatocytes in the liver [9][10][11][12] . There is evidence that some of the liver-specific proteins have temporal suppression in their production during compensatory liver regeneration [5,13,14] .…”
Section: Introductionmentioning
confidence: 99%